1999
DOI: 10.1002/(sici)1097-4628(19990718)73:3<431::aid-app15>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Polymer blends of stereoregular poly(methyl methacrylate) and poly(styrene-co-p-hydroxystyrene)

Abstract: Isotactic, atactic, and syndiotactic poly(methyl methacrylates) (PMMAs) (designated as iPMMA, aPMMA, and sPMMA) were mixed with poly(styrene-co-phydroxystyrene) (abbreviated as PHS) containing 15 mol % of hydroxystyrene separately in 2-butanone to make three polymer blend systems. Differential scanning calorimetry (DSC) and Fourier transform infrared (FTIR) spectroscopy were used to study the miscibility of these blends. The three polymer blends were found to be miscible, because all the prepared films were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 24 publications
(14 reference statements)
1
34
0
Order By: Relevance
“…A simple estimation of the meso and racemic diad fractions was resorted to. The meso and racemic diad fractions of PMMA were estimated previously 12 according to Fernandez-Martin et al 13 or Allen et al 11 The average meso fractions from these two methods are 0.687, 0.338, and 0.093 for iPMMA, aPMMA, and sPMMA, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A simple estimation of the meso and racemic diad fractions was resorted to. The meso and racemic diad fractions of PMMA were estimated previously 12 according to Fernandez-Martin et al 13 or Allen et al 11 The average meso fractions from these two methods are 0.687, 0.338, and 0.093 for iPMMA, aPMMA, and sPMMA, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…One possible cause for the ternary blends rich in iPMMA to be immiscible arises from interactions between iPMMA and PSAN. The explanation was given previously 10 that iPMMA likely forms a more repulsive interaction with styrene or acrylonitrile than aPMMA and sPMMA.…”
Section: Phase Diagrammentioning
confidence: 95%
See 1 more Smart Citation
“…[4][5][6][7][8] Poly(hydroxystyrene) (PHST) and poly(styrene-co-hydroxystyrene) (PST-HST) form miscible blends with various polymers such as poly(alkyl methacrylate), [9][10][11][12][13][14][15][16][17][18][19][20][21] polyesters, [22][23][24][25][26] poly(acrylic acid), [27] and polyethers. [28][29][30] In particular, the blends with poly(alkyl methacrylate) have been widely studied as an attractive hydrogen-bonding interaction system.…”
Section: Introductionmentioning
confidence: 99%
“…Blends of PHS and poly-(methyl methacrylate), PMMA were selected as a model system in this study since hydrogen bonding interactions and miscibility behaviour has been widely reported in the literature. [9][10][11][12][13][14][15][16][17] Indeed, the previous studies on the PHS/ PMMA blend system have detailed its phase behaviour; [11,14] the association mechanism of, and the effect of temperature on, hydrogen bonds; [9,10] its orientation behaviour [15] and the effect of PMMA tacticity on the blend miscibility. [13,17] Physical ageing is the term used to describe the time dependent changes in behaviour in amorphous materials when held at temperatures below the glass transition (T g ).…”
Section: Introductionmentioning
confidence: 99%